1997
DOI: 10.1037/h0087830
|View full text |Cite
|
Sign up to set email alerts
|

Partners of survivors of abuse: A men's therapy group.

Abstract: This article describes a therapy group for the male partners of women in treatment for sexual or physical abuse. The partners came to see themselves as the secondary victims of the original abuse as their relationships and families were disturbed for long periods during their wives' treatment. The group validated the men's experiences, gave them an emotional outlet, educated them about their wives' dynamics, and assisted them in sustaining their relationships. This article presents a typical profile and specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In order to assist the spouse in dealing with the changes in the homeostasis of the couple's system at any stage of therapy, it is recommended that he attend a psychoeducational group for spouses of CSA survivors (Barcus, 1997;Davis, 1991). For the husband who is initially in the rescuer/sane position within the marriage, timing of group participation is not crucial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to assist the spouse in dealing with the changes in the homeostasis of the couple's system at any stage of therapy, it is recommended that he attend a psychoeducational group for spouses of CSA survivors (Barcus, 1997;Davis, 1991). For the husband who is initially in the rescuer/sane position within the marriage, timing of group participation is not crucial.…”
Section: Discussionmentioning
confidence: 99%
“…In extreme, but not necessarily rare, cases the survivor may become unable to relate to the children or, contrarily, may react to them only with anger. In some families, the husband has to take over full responsibility for the house and children for at least part of the duration of the healing process (Barcus, 1997).…”
Section: During the Trauma-work Stagementioning
confidence: 99%
“…Marital relations in the female CSA survivor 291 to take over full responsibility for the house and children for at least part of the duration of the healing process (Barcus, 1997).…”
Section: During the Trauma-work Stagementioning
confidence: 99%
“…As a result, both partners suffer because neither has the permission to express their feelings directly or honestly. Barcus (1997) asserts that most male partners generally suffer si-Iently, vaguely aware of some ill-defined malaise, yet unable or unwilling to articulate it. I n complying with the cultural expectation of a real man who suffers silently in our culture, their feelings of sorrow, pain, and frustration are often denied or suppressed as they endeavor to maintain their lives.…”
Section: Ismentioning
confidence: 99%
“…As a result, the children may, unwittingly, become objects of the displaced emotions by bulk parents. Barcus (1997) reported that in addition to holding full-time jobs, the men in his group often found themselves Compensating €or the survivor's parenting deficits or becoming the primary parent €or extended periods of time. Because the men may not have been initially well bonded to their children, and this is not a role that they were prepared to handle, their parenting skills became another source of contention between thc couple.…”
Section: Ismentioning
confidence: 99%